1998
DOI: 10.1016/s0304-3959(98)00085-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for back pain incidence in industry: a prospective study

Abstract: The objective of this study was to examine the relationship between physical and psychological risk factors on the one hand, and the occurrence of new episodes of back pain on the other hand. A prospective study was conducted with 12 months follow-up by means of self-administered questionnaires. The study took place in the Cargo Department of a major Dutch airline company. The subjects for this study were 270 workers involved in heavy physical work. Only workers without back pain at baseline were included. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 22 publications
5
34
0
Order By: Relevance
“…The results were similar in the entire cohort and in the subgroup without chronic low-back pain in the baseline survey, except for differences regarding age, laying 3DF lime sandstones, and time pressure. The findings are consistent with previous findings according to which a history of low-back pain (25)(26)(27)(28)(29)(30)(31) proved to be important, whereas height, weight, and probably smoking habits were not associated with back disorders in occupational populations (32).…”
Section: Discussionsupporting
confidence: 92%
“…The results were similar in the entire cohort and in the subgroup without chronic low-back pain in the baseline survey, except for differences regarding age, laying 3DF lime sandstones, and time pressure. The findings are consistent with previous findings according to which a history of low-back pain (25)(26)(27)(28)(29)(30)(31) proved to be important, whereas height, weight, and probably smoking habits were not associated with back disorders in occupational populations (32).…”
Section: Discussionsupporting
confidence: 92%
“…The absence of back problems over the study period was found to be significantly less common among those with previous history of back pain. This is in accordance with previous studies in which a history of back pain has been found to be an important predictive factor for future back problems and sick leave [3,18].…”
Section: Discussionsupporting
confidence: 93%
“…The risk was higher among women. Van Poppel et al studied the relationship between physical and psychological risk factors and the episodes of new back pain among workers managing heavy physical loads over a 12-month period [18]. Although none of the factors reached high predictive values, the best were a history of back complaints and low job satisfaction.…”
Section: T Reigo H Tropp T Timpkamentioning
confidence: 99%
“…In spite of this, both previous back injury and >30 days with back pain during the previous year were associated with an increased risk of back injury during follow-up with OR of 1.56 and 1.60, respectively. This shows that even when recurrence is very low, prevention of recurrence or secondary low back pain is important in the return-to-work process for injured workers (8,31).…”
Section: Incidence and Recurrence Of Back Injurymentioning
confidence: 97%